2001
DOI: 10.1017/s0952523801183045
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation and suppression of single striate-cell activity by spatially discrete pattern stimuli presented beyond the receptive field

Abstract: Visual stimulation of a region outside the receptive field of single cells in visual cortex often results in the modulation of their responses. The modulatory effects are thought to be mediated through lateral connections within visual cortex. Research on lateral interactions commonly shows suppression. There has been no systematic study of the optimal conditions for facilitation. Here we have studied the nature of the modulation using a new type of compound stimulus: contrast reversal of pattern stimuli made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 75 publications
10
113
2
Order By: Relevance
“…They also showed that these effects were not due to the flankers encroaching within the distal RF of the recorded cell, but were due to modulatory interactions between cells with non-overlapping distal RFs. Such facilitation is greatest at target contrasts just above the cell's firing threshold (Polat and Norcia, 1996;Polat et al 1998), and includes cases where the flankers are placed at separations of 12 degrees or more (Mizobe et al, 2001), which is beyond the furthest extent of the cell's distal RF (Angelucci et al, 2002). This facilitation is mediated both by long-range intra-regional connections (Stettler et al, 2002) and by feedback from higher regions (Angelucci et al, 2002).…”
Section: Modulation That Amplifies Responses To Rf Inputmentioning
confidence: 99%
“…They also showed that these effects were not due to the flankers encroaching within the distal RF of the recorded cell, but were due to modulatory interactions between cells with non-overlapping distal RFs. Such facilitation is greatest at target contrasts just above the cell's firing threshold (Polat and Norcia, 1996;Polat et al 1998), and includes cases where the flankers are placed at separations of 12 degrees or more (Mizobe et al, 2001), which is beyond the furthest extent of the cell's distal RF (Angelucci et al, 2002). This facilitation is mediated both by long-range intra-regional connections (Stettler et al, 2002) and by feedback from higher regions (Angelucci et al, 2002).…”
Section: Modulation That Amplifies Responses To Rf Inputmentioning
confidence: 99%
“…We found that the absolute magnitude of the gamma‐band response increased with size, despite considerably varying across participants. This stimulus‐dependence, could have important implications for the role of gamma oscillations in neuronal processing [Ray and Maunsell, 2010] and extra‐classical receptive field effects have been shown to depend on stimulus context and spatial configuration, for example, [Akasaki et al, 2002; Mizobe et al, 2001]. Surround suppression is a (well‐known) reduction of neural responses that emerges as the size of the stimulus becomes larger and encroaches on regions outside the classical receptive field [Allman et al, 1985; DeAngelis et al, 1994].…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
“…Therefore, we present results for complex cells only. There is strong evidence that surround suppression operates similarly for simple and complex cells (Dreher, 1972;Rose, 1977;Kato et al, 1978;Nelson and Frost, 1978;Walker et al, 2000;Mizobe et al, 2001;Cavanaugh et al, 2002;Levitt and Lund, 2002). We studied surround suppression in 92 orientation-tuned complex cells.…”
Section: Temporal Characteristics Of Surround Suppressionmentioning
confidence: 99%